PEMENUHAN GIZI PADA BALITA STUNTING MELALUI BUDIDAYA SAYURAN DI DESA BONTOTIRO - Jusni; Sri Ningsih; Yunika Mutmainnah; Sri Mita Wulandari (JMNS, 2019)
The problem of nutrition in childhood is an important problem that must be addressed. Stunting is one of the nutritional problems in the form of a child's height less than the standard. This is the impact of lack of nutritional intake in the first thousand days of life. The purpose of this research is to see the extent to which the nutritional fulfillment of stunting toddlers through vegetable cultivation in Bontotiro Village, Bulukumba Regency. The type of research used is descriptive, which is a method used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the public or generalizations. The results of research conducted in Bontotiro Village, Bulukumba Regency regarding mother's knowledge about stunting, the majority were in the category of poor knowledge of 39 respondents (79.6%). The results of research conducted in Bontotiro Village, Bulukumba Regency regarding the Fulfillment of Nutrition for Stunting Toddlers through Vegetable Cultivation in Bontotiro Village, the majority are in the sufficient category.